Peranan Gereja Terhadap Keluarga Yang Memilih Bercerai Dari Perspektif Konseling Pastoral - Parapat, Riyan Salomo (Sekolah Tinggi Diakones HKBP, 2021)
The church, which is a place of reconciliation for social life, should be able to pay attention to its people, in addition to serving the people with liturgical services, the word of God, and the sacraments, the church should also pay attention to pastoral care. In pastoral care, the Church provides assistance, which is referred to as